DEVELOPING AN INSTRUCTIONAL MATERIAL IN MODEL QUANTUM LEARNING ON SPLTV (International Conference on Social and Islamic Studies, 2022)
The purpose of this research were to (1) know the steps development of module instructional materials with the model Quantum learning on system of linear equation with three variables (SPLTV) (2) know the level of validity, practicality, and effectiveness of developing mathematical module with the model Quantum Learning on system of linear equation with three variables (SPLTV). This research was a Research and Development (R&D). The development model of this research was 4D (Four D Models) which consists of 4 steps, i.e: Define, Design, Develop, and Disseminate. The tryout subject in this research were 25 students in tenth grade of SMA Negeri 2 Tana Toraja. The instruments used in this research were validation sheets, teacher response questionnaires, student response questionnaires, learning achievement tests (THB). The result of this research as follows: (1) The instructional material is very valid because it has an average for each aspect of 4.457 which is at an interval of 4.3  M 5 which is included in the very valid category, (2) Practical because the average percentage of student responses is 84.75% which is in the very good category and the average percentage of teacher responses is 81.25% which is in the good category, (3) is effective because the percentage of completeness of student learning outcomes is 84% ​​in the very good category. Based on the results of the analysis obtained, it can be concluded that instructional materials with the model Quantum Learning on SPLTV have met the criteria of validity, practicality, and effectiveness.